Все лики любви - Алюшина Татьяна Александровна (Еще раз про любовь, 2017)
Экземпляры: Ф 11 (20190614) / Инвентарный номер: 46605 / Цена: 96.00 / Сис.шифр: 84(2Рос=Рус) / Авт.знак: А 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)